Nondestructive Measurement of Photosynthetic Pigments and Nitrogen Status in Jatropha (Jatropha curcas L.) by Chlorophyll Meter - Nyi Nyi; Sridokchan, Weeraphan; Chai-arree, Witith; Srinives, Peerasak (2012)
An experiment was conducted to determine the relationships between a portable chlorophyll meter (SPAD) reading and photosynthetic pigments, leaf N status and chlorophyll fluorescence variables in leaves of jatropha (Jatropha curcas L.). Two thousand and four hundred jatropha leaf discs were prepared and assessed by SPAD reading, UV-vis spectrophotometer, micro-Kjeldahl technique and Pulse Amplitude Modulation (PAM) fluorometry to detect leaf greenness, chlorophyll content, N content and photosynthesis performance, respectively. There were good correlations between SPAD reading and total N concentration (R2=0.99), as well as with content of chlorophyll a (R2=0.97), chlorophyll b (R2=0.96) and carotenoid (R2=0.75). Moreover, there were strong associations between fluorescence variables and SPAD reading. Maximum fluorescence variable (Fm) and maximum quantum efficiency (Fv/Fm) linearly increased with SPAD value and became stable at SPAD value higher than 20 up to 60. The sharp decrease in Fv/Fm when SPAD value was less than 20 refers to the critical point of photosynthesis efficiency in jatropha leaf. Our results clearly showed that SPAD meter can be used to determine leaf N status, photosynthetic pigment concentration and critical photosynthesis efficiency point in jatropha plant.
Keywords: Jatropha